Family Strategy To Fulfill The Needs When Covid-19 Pandemic Disasters Occured - Kartika, Norma Yuni; Normelani, Ellyn; Efendi, Muhammad; Sopyan, Sopyan (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Policies taken by the government to prevent the spread of Covid-19 which is easily contagious have an impact on family income. This research is to determine the strategies undertaken by women in fulfilling their family meet during the Covid-19 pandemic in Andaman Village, Anjir Muara Pasar District, Barito Kuala Regency, South Kalimantan Province. The research method used in this study is a quantitative research method. There were 40 respondents with the sampling using quota sampling method. The data was collected by using a questionnaire which was arranged based on observations before the research was undertaken then the results were analyzed descriptively. The results showed that there were three strategies undertaken by respondents to fulfill their family ends meet during a pandemic, namely related to work, savings, and borrowing money. Related to work, there were three types of activities, namely 5 percent getting a main job, 45 percent getting a side job, and 32.5 percent adding more working hours. Meanwhile 100 percent of respondents started to make savings and 5 percent of respondents borrowed money.